Homo naledi pollical metacarpal shaft morphology is distinctive and intermediate between that of australopiths and other members of the genus Homo. Issue 158 (September 2021) - Bowland, Lucyna A.; Scott, Jill E.; Kivell, Tracy L.; Patel, Biren A.; Tocheri, Matthew W.; Orr, Caley M.
Abstract: Homo naledi fossils from the Rising Star cave system provide important insights into the diversity of hand morphology within the genus Homo . Notably, the pollical (thumb) metacarpal (Mc1) displays an unusual suite of characteristics including a median longitudinal crest, a narrow proximal base, and broad flaring intrinsic muscle flanges. The present study evaluates the affinities of H. naledi Mc1 morphology via 3D geometric morphometric analysis of shaft shape using a broader comparative sample ( n  = 337) of fossil hominins, recent humans, apes, and cercopithecoid monkeys than in prior work. Results confirm that the H. naledi Mc1 is distinctive from most other hominins in being narrow at the proximal end but surmounted by flaring muscle flanges distally. Only StW 418 ( Australopithecus cf. africanus ) is similar in these aspects of shape. The gracile proximal shaft is most similar to cercopithecoids, Pan, Pongo, Australopithecus afarensis, and Australopithecus sediba, suggesting that H. naledi retains the condition primitive for the genus Homo . In contrast, Neandertal Mc1s are characterized by wide proximal bases and shafts, pinched midshafts, and broad distal flanges, while those of recent humans generally have straight shafts, less robust muscle flanges, and wide proximal shafts/bases. Although uncertainties remain regarding character polarity, the morphology of the H. naledi thumb might be interpreted as a retained intermediate state in a transformation series between the overall gracility of the shaft and the robust shafts of later hominins. Such a model suggests that the addition of broad medial and lateral muscle flanges to a primitively slender shaft was the first modification in transforming the Mc1 into the overall more robust structure exhibited by other Homo taxa including Neandertals and recent Homo sapiens in whose shared lineage the bases and proximal shafts became expanded, possibly as an adaptation to the repeated recruitment of powerful intrinsic pollical muscles.